PENGARUH PENAMBAHAN STP COOLER PADA AIR NON COOLANT TERHADAP TEMPERATUR MESIN - Sukri; Syamsuddin, Usman; Merpatih; Musthofa, Imron; Kasmawati (ELEMEN : JURNAL TEKNIK MESIN, 2024)
In general, the engine when running must be in a stable condition. So it is necessary to keep the engine temperature cool during operation, this is very important so that performance is maintained and power is not sluggish. One way is to use a cooler, adding STP Cooler to non-coolant water will certainly reduce engine temperature. The purpose of this study was to determine the effect of using STP Cooler on engine temperature when using plain water and a mixture of plain water and STP Cooler. The method used in this study was to test at 3 variations of engine speed, namely 1000 rpm, 1500 rpm and 2000 rpm. The results obtained show that the average temperature of the engine when using plain water at 1000 rpm engine speed is 65 oC, at 1500 rpm engine speed the temperature is 70 oC, and at 1500 rpm engine speed the temperature is 78.3 oC, while the average temperature when using a mixture plain water with STP Cooler at 1000 rpm rotation the temperature is 70.6 oC, , at 1500 rpm rotation the temperature is 75.3 oC, and at 2000 rpm rotation the temperature is 81 oC, . From the test results it can be concluded that when using ordinary water the average temperature is still lower than when using a mixture of ordinary water and STP Cooler.